The Peninsula Campaign of 1862 : a military analysis - Dougherty, Kevin (University Press of Mississippi, 2005)
The largest offensive of the Civil War, involving army, navy, and marine forces, the Peninsula Campaign has inspired many history books. No previous work, however, analyzes Union general George B. McClellan's massive assault toward Richmond in the context of current and enduring military doctrine. The Peninsula Campaign of 1862: A Military Analysis fills this void. Background history is provided for continuity, but the heart of this book is military analysis and the astonishing extent to which the personality traits of generals often overwhelm even the best efforts of their armies. <